A Review of AI Tutors in Education: Affordances, Challenges, and Emerging Trends - Abubakr Ahmed (Edutechnium Journal of Educational Technology, 2026)
The use of AI tutors has been on the rise in recent years, but very few studies have employed a narrative approach to cover a wide range of tools. This study sought to investigate the affordances, challenges, and emerging trends of AI tutors. A narrative literature review of scholarly sources was conducted in this study. Data were collected by investigating peer-reviewed articles, review articles, book chapters, conference papers, and theses from 2021 to 2026. Results revealed several themes, including utilizing AI tutors for personalized learning support, writing support, overreliance and critical thinking concerns, as well as issues surrounding academic integrity. These results emphasize a balanced approach regarding the adoption of AI tutors that leverages the affordances while minimizing the challenges.